2020
DOI: 10.1002/jlb.4mr0320-488r
|View full text |Cite
|
Sign up to set email alerts
|

Induction of mucosal immunity against pathogens by using recombinant baculoviral vectors: Mechanisms, advantages, and limitations

Abstract: Over 90% of pathogens of medical importance invade the organism through mucosal surfaces, which makes it urgent to develop safe and effective mucosal vaccines and mucosal immunization protocols. Besides, parenteral immunization does not provide adequate protective immunity in mucosal surfaces. Effective mucosal vaccination could protect local and systemic compartments and favor herd immunity. Although various mucosal adjuvants and Ag‐delivery systems have been developed, none has filled the gap to control dise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 186 publications
(274 reference statements)
0
7
0
Order By: Relevance
“…A robust mucosal immune response, characterized by antibody responses in the intestines, would act as a barrier and limit T. gondii transgressions into the epithelial cells. Baculovirus-based vaccines are capable of inducing mucosal immunity against various mucosal pathogens, as demonstrated using the influenza virus and the human papillomavirus ( Fragoso-Saavedra and Vega-López, 2020 ). Consistent with these findings, the ROP4-rBV vaccine generated in this study successfully induced mucosal antibody responses, especially intestinal IgG and IgA which contributed to protection against a lethal dose of T. gondii ME49 infection.…”
Section: Discussionmentioning
confidence: 99%
“…A robust mucosal immune response, characterized by antibody responses in the intestines, would act as a barrier and limit T. gondii transgressions into the epithelial cells. Baculovirus-based vaccines are capable of inducing mucosal immunity against various mucosal pathogens, as demonstrated using the influenza virus and the human papillomavirus ( Fragoso-Saavedra and Vega-López, 2020 ). Consistent with these findings, the ROP4-rBV vaccine generated in this study successfully induced mucosal antibody responses, especially intestinal IgG and IgA which contributed to protection against a lethal dose of T. gondii ME49 infection.…”
Section: Discussionmentioning
confidence: 99%
“…Recombinant viral vectors, including the baculovirus AcMNPV, elicit robust local immune responses when administered intranasally ( 18 , 32 ). To determine the best inoculation route to produce 3BT-specific antibodies in serum and mucosae, mini-pigs were immunized with virions of BacDual-3BT, either utilizing the combined s.c.-i.n.…”
Section: Resultsmentioning
confidence: 99%
“…For PRRSV-2, intranasal and parenteral live-attenuated vaccines have been evaluated, with the risk of mucosal shedding and reversion to virulence ( 95 , 103 , 104 ). Besides, experimental mucosal immunogens based on recombinant proteins, VLPs, or viral vectors have targeted PRRSV-2 surface glycoproteins, with the disadvantage of including decoy epitopes and glycan shields ( 30 , 32 ). Our rationale in choosing the conserved epitope B to design 3BT was based on studies in which peptide-binding and phage-display assays demonstrated that infection-elicited nAbs bind to epitope B in PRRSV-2 ( 75 , 77 , 105 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the intranasal or oral administration of a baculovirus-vectored human papillomavirus (HPV) vaccine conferred protection against vaginal HPV infection [ 50 , 51 ]. Mycobacterium bovis Bacillus Calmette–Guérin (BCG), the only licensed vaccine against TB, has been further developed as vaccine vectors against HIV-1 and SARS-CoV-2 [ 52 , 80 , 81 , 82 ].…”
Section: Challenges and Solutions For The Development Of Mucosa-targe...mentioning
confidence: 99%